A RICH MIN-MAX VEHICLE ROUTING PROBLEM - Ertan YAKICI (Journal of Naval Science and Engineering, 2016)
We present a new variant of vehicle routing problem with a min-max objective function. The problem has different types of service demands satisfied by a heterogeneous ﬂeet of vehicles. Unlimited service capacitated vehicles serve the demand points with multiple time windows and requirement of operation synchronization when demand is split between vehicles. A mixed integer linear programming based heuristic solution approach is proposed and a numerical study is carried out to assess the performance of the proposed method.